Artificial Intelligence Based Portable Robot Device for Autonomous Venepuncture - Nadiminti Venkata Ramana Murty; Sireesh Aryasomayajula (International Journal of Advanced Robotics and Automation Technology, 2024)
Venepuncture is a source of medical hurt and is necessary for a wide range of therapeutic procedures. Venpuncture-related complications worsen in difficult settings, where the success rate is largely dependent on the physiology of the patient and the skill of the practitioner. It is difficult to find the vein for infants, adolescent girls, obese and elderly people and it is causing severe pain in the traditional manual blood drawing system. In this research work, a novel idea entitled “Artificial Intelligence based Portable Robot for Autonomous Venepuncture (AIPRAV)” is proposed that can automatically detect the Human Vein, Inserts Needle and Draws pre-defined amount of blood without causing any pain (by spraying local anesthesia) and without any human intervention. By creating a peripheral line for both IV drugs and blood draws, this automated equipment promotes procedure safety and accuracy. The apparatus comprises a robotic needle, computer vision software, and a near-infrared imaging system all enclosed in a portable shell. An LCD display allows users to view the device's real-time activity progress. In order to guide the needle into an exact vein, the gadget works by imaging and recording the 3D spatial coordinates of superficial veins in real-time.
Keywords: Autonomous Venepuncture; Portable Robot; Venepuncture; artificial intelligence